A preliminary checklist of harvestmen (Arachnida: Opiliones) in Malaysia - Fatin Elina Kamarulzaman; Dzulhelmi Muhammad Nasir; Nur Syahirah Mamat; Izfa Riza Hazmi; Faszly Rahim (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by Scopus